The European Union’s Quest for Energy Policy: A Geo-Economic Approach - Alin Codoban (Romanian Journal of European Affairs, 2011)
The European Union’s external energy policy architecture is very important for further energy security and economic development. European normative power on its neighbours represents the most efficient way of integrating neighbouring energy markets, with the EU’s emerging internal market and, in perspective, through economic interdependence and complementarities, there are chances of creating an European geo-energy space. EU’s tools for shaping the geoenergy space are becoming more effective in an extended European economic area that would allow it to act as the main actor in a multilateral interconnected system of energy producer and transit countries. The result of the paper is materialized in a new paradigm for EU’s external energy policy, which can provide future security of supply through market institutions and an active economic diplomacy in the resource energy countries.